Effect of V content on corrosion behavior of high-energy ball milled AA5083. (1st July 2021) - Esteves, L.; Christudasjustus, J.; O'Brien, S.P.; Witharamage, C.S.; Darwish, A.A.; Walunj, G.; Stack, P.; Borkar, T.; Akans, R.E.; Gupta, R.K.
Highlights: Ball milled AA5083 with V addition showed superior pitting corrosion resistance. Nanocrystalline, homogenous microstructures were achieved using ball milling. No major influence of V addition on the composition of passive film. Abstract: AA5083 alloys with V additions were produced in the powder form by high-energy ball milling and consolidation by spark plasma sintering and cold compaction. X-ray diffraction and energy dispersive X-ray spectroscopy analysis indicated the formation of supersaturated solid solution and grain refinement below 100 nm. Corrosion behavior was investigated using electrochemical impedance spectroscopy, cyclic potentiodynamic polarization, and immersion corrosion tests followed by surface analysis. The composition of the passive film was obtained via X-ray photoelectron spectroscopy. The corrosion resistance of the AA5083 was significantly improved due to the addition of V and high-energy ball milling.